Pengaruh Independensi Dan Persepsi Junior Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik Jakarta Pusat Yang Sudah Terdaftar Di OJK - Riyan Setiawan; Novawiguna Kemalasari (Jurnal Pena-Mas Akuntansi, 2022)
The purpose of this study was made to test and find out whether there is an influence between Independence and Junior Auditor's Perception of Audit Quality. This research was conducted by taking samples from auditors who are in Central Jakarta Public Accounting Firm. By using the questionnaire as a testing tool and PLS as a data processing tool from the questionnaire. The results of the study prove that Independence influences Audit Quality because auditors who are in Central Jakarta Public Accountant Firms do not violate the established audit profession standards while Junior Auditor's Perception does not affect audit quality because audit implementation does not affect the perception between audit quality and the results produced